Persistence of underdevelopment: Does the type of natural resource endowment matter? - Maiju Perälä (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2003)
This paper examines growth successes and failures across countries and notes the latter's perplexing predominance among ex ante low-income economies. An explanation for this persistence of underdevelopment is proposed through an empirical investigation that brings forth evidence on the importance of natural resource endowment type on growth or, more appropriately, lack of it. The results show that, in the absence of social cohesion, the nature of natural resource abundance bears great significance as a natural resource endowment characterized by oil and/or mineral resources is more negatively correlated with growth than a resource endowment that is agricultural. The robustness of this result is tested across a number of growth regression specifications within the literature.
Keywords: O13; O47; O50; 330; agricultural and natural resource economies; development; growth; natural resources; underdevelopment; cross-country studies; Unterentwicklung; Wirtschaftswachstum; Natürliche Ressourcen; Welt